INOVASI PEMBELAJARAN INTERAKTIF DI TKB RAINBOW KIDS MELALUI PELATIHAN APLIKASI QUIZIZZ BAGI GURU - Saputri, Galuh; Ester, Ria (JAMAIKA: JURNAL ABDI MASYARAKAT, 2025)
This Community Service (PkM) activity was carried out at Rainbow Kids Kindergarten as an effort to improve teacher competency in implementing interactive learning based on digital technology. The problem faced by partners was the limited use of interactive digital learning media, so the learning process was not optimal in increasing student engagement and motivation. The purpose of this activity was to provide training on the use of the Quizizz application to teachers as a fun interactive learning innovation that is appropriate to the characteristics of early childhood. The implementation method included socialization, material delivery, demonstration of application use, hands-on practice in creating interactive quizzes, and activity evaluation. The implementation results showed an increase in teacher understanding and skills in designing and implementing game-based learning. In addition, teachers became more creative and innovative in compiling interesting and participatory learning materials. This activity is expected to contribute to improving the quality of learning and supporting digital transformation in early childhood education environments.